The Role of Customer Journey Mapping in Digital Business Development - Togale, Manoj (Journal of Global Economy, Business and Finance, 2026)
This study outlines all stages of implementing the Customer Journey Map (CJM) system in business and proposes a set of solutions for its systematization. It also examines the key stages a potential customer undergoes on the path to making a purchase, along with potential challenges they may encounter. The research covers essential aspects of CJM implementation, such as touchpoints, customer interviews, pain points, and customer emotional responses. As a result of the study, it is concluded that utilizing CJM enables business owners to gain a deeper understanding of their customers, thereby improving service quality. Additionally, a correlation is identified between analyzing the target audience and the efficiency and profitability of a business. Customer expectations regarding interactions with a company are analyzed, leading to the conclusion that customer - centricity is of paramount importance. This article may be particularly useful for entrepreneurs seeking to enhance the efficiency of their businesses and for emerging companies aiming to establish their niche.